Managing estuaries under a changing climate: A case study of the Humber Estuary, UK. Issue 134 (August 2022) - Lonsdale, Jemma-Anne; Leach, Chloe; Parsons, Dan; Barkwith, Andrew; Manson, Susan; Elliott, Michael
Abstract: Estuaries are globally important zones for urban, recreational and commercial activities as well as supporting a range of habitats and species of significant ecological importance. The role of estuaries is recognised by the legislative framework that has been developed to protect and manage these areas as well as those species and resources in adjoining habitats. However, estuaries worldwide are subject to a number of major threats, including increasing industrialisation and urbanisation, increasing resource scarcity notably for space and energy, and the impacts of climate change, sea-level rise and related increases in vulnerability and decreases in resilience. In addition to local pressures, climate change is now increasingly recognised as having a range of severe impacts on estuarine ecosystem functions and services, but current legislation and associated management may not necessarily be wholly appropriate to deal with these longer-term changes. Here we consider how the current legislation and management addresses the potential impacts of climate change on a large estuarine system. Alongside a set of recommendations, we emphasise that the implementation of governance instruments needs to be underpinned by continued monitoring, improved modelling and enhanced predictive capabilities and integration and collaboration across management levels. Highlights: We provide a review of the potential impacts from climate change on estuaries. The current management measures for managing these impacts are presented. Future approaches to legislation are recommended.